Monitoring Tacrolimus Concentrations in Whole Blood and Peripheral Blood Mononuclear Cells: Inter- and Intra-Patient Variability in a Cohort of Pediatric Patients - De Nicolò, Amedeo; Pinon, Michele; Palermiti, Alice; Nonnato, Antonello; Manca, Alessandra; Mula, Jacopo; Catalano, Silvia; Tandoi, Francesco; Romagnoli, Renato; D’Avolio, Antonio; Calvo, Pier Luigi (Frontiers in Pharmacology, 2021)
Tacrolimus (TAC) is a first choice immunosuppressant for solid organ transplantation, characterized by high potential for drug-drug interactions, significant inter- and intra-patient variability and narrow therapeutic index. Therapeutic Drug Monitoring (TDM) of TAC concentrations in whole blood (WB) is capable to reduce the incidence of adverse events. Since TAC acts within lymphocytes, its monitoring in peripheral blood mononuclear cells (PBMC) may represent a valid future alternative for TDM. Nevertheless, TAC intracellular concentrations and their variability are poorly described, particularly in the pediatric context. Therefore, our aim was describing TAC concentrations in WB and PBMC and their variability in a cohort of pediatric patients undergoing constant immunosuppressive maintenance therapy, after liver transplantation. TAC intra-PBMCs quantification was performed through a validated UHPLC–MS/MS assay over a period of 2-3 months. Twenty-seven patients were included in this study. TAC changes in intracellular concentrations were not statistically significant (p=0.710), with a median percent change of -0.1% (IQR -22.4% – +46.9%) between timings: this intra-individual variability was similar to the one in WB, -2.9% (IQR -29.4 - +42.1; P =0.902). Among different patients, TAC weight-adjusted dose and age appeared significant predictors of TAC concentrations in WB and PBMC. Intra-individual seasonal variation of TAC concentrations in WB, but not in PBMC, have been observed. These data show that the intra-individual variability in TAC intracellular exposure is comparable to the one observed in WB. This opens the way for further studies aiming at the identification of therapeutic ranges for TAC intra-PBMC concentrations.